Development of Learning Media Gamification Based on Gamimath Android in Mathematics Learning for Elementary School - Sigit Dwi Laksana; Anip Dwi Saputro; Ayok Ariyanto; Dirga Ayu Lestari (UIN Sunan Kalijaga Yogyakarta, 2024)
The application of technology in the learning process can be a creative innovation. The use of Gamimath is a strategic step that teachers can develop. The purpose of using Gamimath is to facilitate students learning while being able to increase student involvement in the learning process, Which combines the element of gamification with mathematics learning. Where The purpose of this study is to develop learning media assisted by the GAMIMATH application, especially in mathematics subjects, and provide convenience in the mathematics learning process for students so that no one will say mathematics is challenging to understand learning. This research and development (R&D) project consists of six stages: analysis, design, development, implementation, and evaluation. The subject of this research is PGMI students in the second semester of the Faculty of Islamic Religion, University of Muhammadiyah Ponorogo. The results of this research are that the game math application product has been produced. Based on the results of the validation test by the expert team, it received a score of 85 out of a maximum score of 90 with the category of very good and decent. In addition, during the test, the N-gain Score was 56, which means that the use of the Gamimath application has proven to be quite effective in Improving students' understanding of learning, such as solving problems related to mathematics, collaborating with friends in finding answers to the problems given by following each step in the existing application and solving the challenges given.